Productivity Assessment and Schedule Compression Index (PASCI) for project planning - Mansur, Shaiful Amri (2003)
Planning and scheduling of construction projects are very much affected by its resource productivity and influenced by various other factors. An increase in construction time and cost is usually related to inefficiency or low productivity, which can be reduced by employing effective planning and monitoring. Schedule compression or work acceleration whether it is planned or unplanned, is normally required to recover projects from delay and inefficient works. It is not easy to perform schedule compression for people who do not have good knowledge and experience on construction processes. The situation can become very difficult and discouraging for many small contractors, especially during economic downturns. There is a need for a simple way to assess productivity and apply schedule compression by using simplified tools such as an index. This paper discusses an on-going research, which objective is to produce a project assessment tool called the Productivity Assessment and Schedule Compression Index (PASCI). This index utilizes a combination of weighted scores from key elements that affect labour productivity and schedule compression methods. It predicts the capability of completing a construction project by comparing the index score to its given contract period at a certain stage of a project. Using the index as a guide, further actions can be taken by contractors and clients, which could produce savings in terms of time and cost.